METTL3-Mediated N6-Methyladenosine Modification Is Involved in the Dysregulation of NRIP1 Expression in Down Syndrome - Shi, Weili; Yang, Fan; Dai, Ranran; Sun, Yafei; Chu, Yan; Liao, Shixiu; Hao, Bingtao (Frontiers in Cell and Developmental Biology, 2021)
Down syndrome (DS) is a common genetic condition in which a person is born with an extra copy of chromosome 21. Intellectual disability is the most common characteristic of DS. N6-methyladenosine (m6A) is a common RNA modification that is implicated in many biological processes. It is highly enriched within the brain and plays an essential role in human brain development. However, the mRNA m6A modification in the fetal brain of DS has not been explored. Here, we report m6A mRNA profiles and mRNA expression profiles of fetal brain cortex tissue from DSs and controls. We observed that the m6A modification in DS brain tissues was reduced genome-wide, which may be due to decreased the m6A methyltransferase like 3 (METTL3) protein expression. The nuclear receptor-interacting protein 1 (NRIP1/RIP140) is coded by a highly conserved chromosome 21 (Hsa21) gene. Overexpression of NRIP1 is associated with mitochondrial dysfunction in DS. The NRIP1 mRNA increased in fetal brain tissues of DS, whereas the m6A modification of the NRIP1 mRNA significantly decreased. METTL3 knockdown reduced the m6A modification of NRIP1 mRNA and increased its expression, and an increase in NRIP1 m6A modification and a decrease in its expression were observed in METTL3-overexpressed cells. The Luciferase reporter assay confirmed that METTL3 regulates NRIP1 expression in an m6A-dependent manner. The decay rate of NRIP1 mRNA was significantly reduced in METTL3-knockdown cells but increased in METTL3-overexpressed cells. We proposed that the m6A modification of NRIP1 mRNA in DS fetal brain tissue is reduced, reducing its transcript degradation rate, resulting in abnormally increased expression of NRIP1, at least partially, in the DS brain. It provides a new mechanism for the molecular pathology of DS and leads to a new insight that may become therapeutically relevant.